2021
DOI: 10.2166/ws.2021.084
|View full text |Cite
|
Sign up to set email alerts
|

Ground water toxicity due to fluoride contamination in Southwestern Lahore, Punjab, Pakistan

Abstract: The prevalence of dental/bone deformities provides motivation for studying the distribution, severity and sources of the Fluoride (F−1). The ground water samples (n = 77) were collected, from the districts of Lahore and Kasur of approximately 750 Km2 area. The water was analyzed for fluoride (F−), pH, electric conductivity (EC), alkalinity and hardness. The results revealed F− concentration ranges from 0.25–21.3 mg. An inverse relation between depth and fluoride concentration was observed. On the basis of clus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 58 publications
0
0
0
Order By: Relevance
“…Evidence indicates that F-concentration depends on the depth of the well; shallow wells are highly vulnerable to anthropogenic activities such as agricultural activities [33]. However, another study reported that the F-level decreases with increment of well depth [34]. In our study, the Adama dry season maximum F-level was 3.55mg/L while the wet season was 1.49 mg/L.…”
Section: Discussioncontrasting
confidence: 41%
“…Evidence indicates that F-concentration depends on the depth of the well; shallow wells are highly vulnerable to anthropogenic activities such as agricultural activities [33]. However, another study reported that the F-level decreases with increment of well depth [34]. In our study, the Adama dry season maximum F-level was 3.55mg/L while the wet season was 1.49 mg/L.…”
Section: Discussioncontrasting
confidence: 41%
“…Таким чином, забруднення ґрунтових вод фтором на досліджуваній території було спричинене проникненням промислових стічних вод. Нещодавно зареєстровано деформації кісток у 1,51 мільйона населення, які проживають у західній частині провінції Пенджаб і можуть бути пов'язані з підвищеною токсичністю фтору в цьому районі [34].…”
Section: результати дослідження та їх обговоренняunclassified